Effect of breed, parity number, and location on productive and reproductive parameters of dairy cattle - Rúa-Giraldo, Cristian-Camilo; López-Herrera, Albeiro; Ruiz-Cortés, Tatiana (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Productive and reproductive parameters of dairy cattle in the high tropics are affected by various factors related to management, but also by specific factors such as breed, calving, and herd location. Objective: To analyze the effects of breed, calving, and location on herd efficiency by assessing productive and reproductive information from dairy herds in Antioquia province (Colombia). Methods: Productive and reproductive information from 5,440 records of cows between 1 and 11 calvings and various breeds and crosses was obtained. The animals belonged to 57 herds from 16 municipalities in three dairy regions of Antioquia province: North-N, East-E, and Valle de Aburrá-V. The variables analyzed were milk production adjusted to 305 days (PLa), kilograms of protein per lactation (KgPRO), kilograms of fat per lactation (KgF), somatic cell score (SCS), number of services per conception (S/C), days open (DO), and calving interval (CI). The independent variables were associated with the parameters through a generalized linear model (GLM). Results: The total PLa average was 5,492.6 (±1,027.2) kg/lactation. The values were 177.1 (±29.5) and 215.1 (±37.1) kg/lactation for KgPROa and KgFa, respectively. For SCS, an average value of 3.62 (±1.6) was found. Reproductive parameters were 2.02 (±1.4), 385.7 (±52.8) days, and 110.9 (±55.4) days for S/C, CI, and DO, respectively. Ayrshire × Holstein cows from region V, presented low PLa (58%). Holstein cows in their third parturition presented low PLa (31%), somewhat similar to the decrease in PLa of Ayrshire in second calving (56%). Furthermore, decreased milk production was observed in Angus × Holstein cows (46% less PLa) and in Brown Swiss in region V, with 41% less milk per lactation. The KgFa data decreased when compared to the general average, with values of 172.9±24.7 kg for Holstein, 132.5±46.2 kg for Ayrshire × Holstein in E region, and 102.2±26.5 kg in Ayrshire × Jersey cows. The longest CI was significantly (p<0.05) associated with the third parity and with the Holstein breed (37% increase) and with BON × Holstein crosses (57% increase). Conclusions: Productive and reproductive parameters are variable, and multiple interacting independent variables –such as breed, parity and location- lead to decrease or increase in the studied parameters.